Innovative Mechanisms to Counteract Risks and Threats to Foreign Economic Security of the Region - Anatolievna Kulagovskaya, Tatyana; Alexandrovna Ter-Grigoryants, Anna; Vladimirovna Maslennikova, Natalia; Nikolaevna Kovtun, Evgenia; Vladimirovna Slavnetskova, Lyudmila (International Journal of Engineering and Technology, 2018)
The article assesses the impact of internal and external factors on the economic security of the region in foreign trade activities. Negative consequences of the foreign economic activities on economic security of the Stavropol Territory are analyzed. Types of the risks enterprises may face when entering the foreign market are considered. Protectionist arguments in favor of pursuing a free trade policy are presented and argued, which implies a staged formation of a mechanism to efficiently counteract threats to the external economic security of the region.The study considers the level and dynamics of the main macroeconomic indicators of the subjects of the North Caucasus Federal District as compared to the average Russian achievements, the resource potential, problems of the economic development of the macroregion, prerequisites for the formation of the state policy on supporting the region. It substantiates the top priority directions of long-term socio-economic development of subjects in order to overcome the pervasive arrearage of the economy and social area.Â Â